Associations Between Chronic Rhinosinusitis and Cancers: A Nationwide Population‐Based Cohort Study. (19th May 2022) - Jeon, Yung Jin; Joo, Yeon‐Hee; Cho, Hyun‐Jin; Kim, Sang‐Wook; Park, Bumjung; Choi, Hyo Geun
Abstract : Objective: Chronic rhinosinusitis (CRS) is one of the most common chronic inflammatory diseases. The effect of chronic inflammation caused by CRS on the occurrence of various cancers has not been thoroughly evaluated. This study aimed to investigate the increased incidences of 10 types of cancers among CRS patients with/without nasal polyps (NP) using a national population‐based database from the Korean Health Insurance Review and Assessment Service. Study Design: A case–control cohort study. Methods: We compared the prevalence of various comorbidities between CRS and control participants from a national cohort dataset of the Korean Health Insurance Review and Assessment Service. Methods: CRS participants ( n  = 6, 919) and non‐CRS ( n  = 27, 676) participants were selected from among the 514, 866 participants from 2002 to 2015. A stratified Cox proportional hazards model was utilized to assess the hazard ratio (HR) of CRS for 10 types of cancers. Results: A stratified Cox proportional hazard model demonstrated that the adjusted HR for hematologic malignancy was significantly higher in the CRS patients than in the controls regardless of the presence of NP (2.90 for total CRS; 2.15 for CRS with NP; 4.48 for CRS without NP). The HR for thyroid cancer was significantly higher in the CRS patients without NP but not in those with NP (1.50 for total CRS; 1.78 for CRS without NP). Conclusion: This study showed that CRS participants had a significantly higher prevalence of hematologic malignancy and thyroid cancer. Level of Evidence: 4 Laryngoscope, 133:1044–1051, 2023 Abstract : The current study investigated whether CRS is significantly associated with the incidences of various cancers. CRS was associated with an increased incidence of hematologic malignancy and thyroid cancer.